INNOVATIVE APPROACHES TO DETECTING AND REMOVING TRACES OF BIOLOGICAL ORIGIN ON PROPRIETARY EVIDENCE - Yanchuk A.О.; Kryvda, R.H.; Katerynchuk, I.P.; Kuznichenko, S.O.; Zaiets, O.M. (World of Medicine and Biology, 2019)
The purpose of the work was to develop an integrated methodological approach to conducting a forensic examination to identify micro quantities, micro traces, contact traces of biological origin using modern molecular genetic methods. In the process of committing a crime, the offender is in direct contact with the body of the victims, their clothing, and other objects of the environment, resulting in invisible (latent) traces. The complexity of the complete destruction or falsification of traces of biological origin increases the proportion of these traces in the system of physical evidence. Used for identification purposes, this evidence is most reliable and significant both in exposing reasonably suspects and in establishing non-involvement in the crimes of innocent persons. The widespread introduction and application of methods to identify and investigate invisible (latent) DNA-containing traces will lead to an increase in the disclosure of grave and especially grave crimes, including the disclosure of crimes of past years. Mastering and improving this area of research is one of the highest priorities of the forensic genetic examination.